Strategi Pengembangan Perikanan Tangkap di Kabupaten Pemalang - Amelia Maghfiroh; Agustina Setyaningrum; Edy Masduqi (Jurnal Perikanan Unram, 2024)
Pemalang Regency is one of the regencies that has abundant capture fisheries potential. However, there are several problems in developing capture fisheries. This research aims to identify and assess internal and external factors in the development of the capture fisheries sector and to develop a strategy for developing capture fisheries in Pemalang Regency. This research uses SWOT (Strength, Weakness, Opportunity, and Treat) analysis to develop a development strategy. The data collected includes primary data and secondary data. The research results show that the value of Internal Strategic Factors Analysis Summary (IFAS) and External Strategic Factors Analysis Summary (EFAS) have a positive value so it is in Quadrant I. Based on this, an aggressive strategy is the main priority in developing capture fisheries in Pemalang Regency.